Avaliação da atividade do extrato de Herissantia tiubae (K. Schum) Brizicky no processo inflamatório agudo - Lima, Ana Luisa de Araujo (2014)
The species Herissantia tiubae ( K. Schum ) Brizicky, popularly known as mela-bode or lava prato , is a plant of Malvaceae family, used in folk medicine to treat fever and influenza. Other species of the Malvaceae family are used in traditional medicine and studies have shown anti-inflammatory, antinociceptive and diuretic activities. The aim of this study was to evaluate the activity of the hydroalcoholic extract of aerial parts of Herissantia tiubae (EHt) in experimental models of acute inflammation. The toxicity of EHt at dose of 2000 mg/kg was analyzed using the parameters: consumption of water and food, body weight, mortality and rates of weight of major organs, as well as biochemical and hematological parameters. To evaluate its antiedematogenic effect, Swiss mice pretreated with EHt (50, 100 or 200 mg/kg), were submitted to the paw edema induced by carrageenan and microvascular permeability induced by acetic acid protocols. To study its anti-inflammatory effect in vivo experimental models were used, such as: carrageenan-induced peritonitis, which evaluated cell migration and cytokine production (TNF-α, IL-1β and IL-6) and in vitro: production of NO, cytokines (TNF-α and IL-6) and L- selectin expression in RAW 264.7 macrophage lineage. No signs of acute toxicity were observed by the administration of EHt in male and female mice. Furthermore, pretreatment with EHt (50, 100 or 200 mg/kg) did not reduce paw edema induced by carrageenan, and did not decrease fluids extravasation mediated by acetic acid. Migration of neutrophils and release of cytokines (TNF-α and IL-1β) induced by carrageenan was reduced in animals treated with EHt (50 or 100 mg/kg). In vitro, EHt (50 or 25 μg/mL) reduced the production of NO, cytokines (TNF-α and IL-6) and expression of the adhesion molecule L-selectin in RAW 264.7 macrophages lineage. Therefore, these data suggest that EHt has antiinflammatory activity related to inhibition of cellular but not by vascular events of inflammation